(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Hand gesture detection is a project which recognizes the gesture of hands and detect accordingly. Hand Gesture recognition is an important technique for creating user-friendly interfaces. Hand gesture is recognized by robots, for example, can take human commands, and those who are deaf or who cannot speak, can recognize the sign language for communication. Hand gesture recognition in video games could help by allowing players to use gestures to interact with the game rather than a controller. Moreover, to account for the infinite number of possible hand positions in three dimensions, such an algorithm must be more robust. It must also be capable of working with video rather than static images.